Pembelajaran Seni Budaya di SMA Negeri Marga Baru Kecamatan Muara Lakitan - Ilhaq, Muhsin; Kurniawan, Irfan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is a research on learning art and culture in high school, new clan. The approach inthis study uses a qualitative descriptive method. In this case, it will describe the process of learningarts and culture including discussions about planning, implementing and evaluating learningcarried out by teachers as the main element in the process. Data was collected through directobservation in the field, structured interviews, and collecting documents related to the learningprocess. Furthermore, data analysis was carried out using triangiulation techniques, then presented analytically descriptively. Based on the data analysis, the results of the research show that teachers have the ability to design learning, implement and develop theater learning well.